THE EFFECT SELF EFFICACY, FUTURE ORIENTATION STUDENT LEARNING ATTENTION, TEACHER ATTTUDES, AND SCHOOL ENVIRONMENT ON STUDENTS INTEREST IN CONTINU- ING THEIR EDUCATION TO HIGHER EDUCATION AMONG TO HIGHER EDUCATION AMONG 11TH GRADE STUDENTS AT SMK NEGE - Fajri, Hidayatul; Jimi Ronald; Fifi Yasmi (Global Action and Education for Society, 2025)
This study aims to determine (1) the effect of self-efficacy on students' interest in continuing their education to college (2) the effect of future orientation on students' interest in continuing their education to college (3) The effect of students' learning attention on their interest in continuing their education to higher education (4) The effect of teachers' attitudes on students' interest in continuing their education to higher education (5) The effect of the school environment on students' interest in continuing their education to higher education. The research was conducted in July 2025. This research is an associative study. The population in this study is students at SMK Negeri 1 Bonjol. The sample consists of 94 people using stratified random sampling. The data analysis techniques used are descriptive and inductive analysis, with the assistance of Eviews 8 and SPSS version 20.0. The results of this study indicate that: 1) self-efficacy has a significant effect on interest in continuing education to higher education, with a coefficient value of 0.396 and a t-value > t-table (4.705 > 1.66235). 2) Future orientation significantly influences students' interest in continuing their education to higher education, with a coefficient value of 0.221 and a calculated t-value > table t-value (2.194 > 1.66235). 3) Student learning attention significantly influences students' interest in continuing their education to higher education, with a coefficient value of 0.212 and a t-value > t-table (2.076 > 1.66235). 4) Teacher Attitude (X4) has a significant effect on students' interest in continuing their education to higher education, with a coefficient value of -0.324 and a calculated t-value > table t-value (-3.526 > 1.66235). 5) School environment significantly influences students' interest in continuing their education to higher education, as indicated by a coefficient value of 0.388 and a t-value > t-table (4.202 > 1.66235). 6) Self-efficacy, future orientation, student learning attention, teacher attitude, and school environment collectively significantly influence students' interest in continuing their education to higher education, as evidenced by the calculated F value of 16.322 > F table 2.36 and a significance level of 0.000 < 0.05.